Potential uses of Adhatoda Vasica in orthodontics - Murukesan Subramanian; Kishore Kumar Selvaraj; Raghunathan Jagannathan; Swaminathan Rajendran; Deepika Rajendran; Balaji Thodur Madapusi (Wolters Kluwer Medknow Publications, 2023)
Plaque control, pain control, and modulation of inflammatory mediators to accelerate or stabilize tooth movements are hot issues in orthodontics. The recent advent of phytochemicals as biological mediators has opened new vistas in the aforementioned areas of orthodontics. Adhatoda vasica has caught the attention of investigators due to multiple properties related to orthodontics. This study addresses the potential areas of use of A. vasica in orthodontics, which provide ideas for further investigations. A. vasica possesses antibacterial activity, antifungal activity, anti-oxidant effect, anti-inflammatory activity, analgesic effect, osteogenic, and osteoclastic activities. A. vasica has huge potential in orthodontics, whereas all these vistas need careful and methodical testing before use in clinical orthodontics. In the future, investigators can focus on these aspects of the use of A. vasica to develop products.